IT re-implementation project. A multiple case study analysis - Wachnik, Bartosz (Informatyczne projekty reimplementacyjne. Analiza studiów przypadków, 2017)
A high number of IT implementation projects still end in failure or only partial success. Some IT projects, however, are terminated already during project completion due to unsatisfactory progress of work or other organisational problems affecting the project. Particularly noteworthy are re-implementation projects, where an MIS is implemented again. The aim of this article is to present a characteristic of a re-implementation-type IT project consisting in an MIS-class system implementation. The author presents the results of his research conducted with the multiple case study method. The conclusions may be interesting both for practitioners and theoreticians of business informatics specialising in IT project completion
Informatyka Ekonomiczna = Business Informatics, 2017, Nr 1 (43), s. 86-97
Keywords: MIS; re-implementation; IT; project; reimplementacja